Chemicals Ethylene Polyethylene / Nur Ain Nadhirah Anuar - Anuar, Nur Ain Nadhirah (Perpustakaan Tengku Anis, 2017)
This special project based on the period from 1st February 2017 until 29th June 2017 in Maintenance Department at Pertonas Chemicals Ethylene, Terengganu. The trainee is placed in Reliability and Integrity Management Sections (RIMS) under the supervision of Mrs Nadia Binti Ithnin which is a statisticians. The trainee is assigned to develop a form (impermenant inventory) as the special project which is SAP Master Data Update Request. Basically the is SAP Master Data Update Request is being considered in order to improve the level of management of handling an equipment in plant or site. Before this, they use traditional method so that it is such an ineffective way. However, the trainee also involved with other activities and programs which each of them gave new experience and gained a lot of knowledge. Throughout the industrial training session, the trainee had improved a lot of skills such as communication skill, problem solving, self-learning, teamwork and others. The industrial training session are going well until the end of the day. The staff in Petronas Chemicals Ethylene gave a very good cooperation with the trainee during the industrial training session.